Implementing Green Marketing Communication Strategies to Build Corporate Reputation and Consumer Trust: A Qualitative Case Study Orientation in Manufacturing Companies in Tangerang City - Inva Jaswita, Derizka; Aspiranti, Tasya; Amalia, Ima; Nurhayati, Nunung (Publisher Cv. Inara, 2026)
Environmental sustainability communication has become an essential corporate strategy, particularly within manufacturing sectors in emerging economies. This study explores how manufacturing companies in Tangerang City, Indonesia, implement green marketing communication strategies and how these strategies influence corporate reputation and consumer trust. Using a qualitative multiple-case study approach, data were collected through semi-structured interviews with 27 participants, including marketing managers, sustainability officers, consumers, NGO representatives, and government officials, supplemented with document analysis and field observations. Thematic analysis identified three dominant communication strategies: informational, emotional, and participatory green communication. The credibility of these strategies is shaped by transparency, message consistency, evidence-based claims, and alignment between communication and environmental practices. Findings reveal that firms adopting high-transparency green communication experience stronger reputation enhancement and improved consumer trust, while firms with inconsistent environmental performance face skepticism and accusations of greenwashing. A conceptual model is proposed describing the pathways through which green communication enhances trust and reputation. This study contributes to the literature by integrating signaling theory, green marketing theory, and trust theory to explain communication credibility in the context of developing countries. Practical implications are offered for manufacturers seeking to strengthen sustainability communication and legitimacy.